(untitled) (Fenestella. Inside Medieval Art, 2022)
The paper deals with the development and settlement of female monasteries in the urban contexts of the early Middle Ages. Through a preliminary focus on the community founded by saint Cesarius in Arles during the 6th century, the article aims to identify some elements recognizable in this context and to investigate them in other towns. Important aspects like the liturgical organization of different oratoria, the placement of the burial church for the female community, and the role in the promotion of saints’ cult during the high Middle Ages represent an interesting possibility of comparison, in this case with the reality of Metz, specifically with Saint-Pierre-aux-Nonnains and Sainte-Glossinde. The last part of the paper is dedicated to a first analysis of the role and spatial organization of female monasteries in two Lombard towns: Milan and Pavia. Through a survey of the communities already existing in the 11th century and their position in the urban topography the paper opens to some remarks following the observations made for Arles and Metz, thus suggesting the necessity of an in-depth study of these north-Italian contexts.